Subaru/HSC identifications of protocluster candidates at z ∼ 6–7: Implications for cosmic reionization. Issue Volume 15:Issue S341(2019) (November 2019) - Higuchi, Ryo; Ouchi, Masami; Ono, Yoshiaki; Shibuya, Takatoshi; Toshikawa, Jun; Harikane, Yuichi; Kojima, Takashi; Chiang, Yi-Kuan; Egami, Eiichi; Kashikawa, Nobunari; Overzier, Roderik; Konno, Akira; et al.
Abstract: We report fourteen and twenty-eight protocluster candidates at z = 5.7 and 6.6 over 14 and 19 deg 2 areas, respectively, selected from 2, 230 Lyα emitters (LAEs) photometrically identified with Subaru/Hyper Suprime-Cam (HSC) deep images. Six out of the 42 protocluster candidates include at least 1 spectroscopically confirmed LAEs at redshifts up to z = 6.574. By the comparisons with the cosmological Lyα radiative transfer (RT) model reproducing LAEs with the reionization effects, we find that more than a half of these protocluster candidates might be progenitors of the present-day clusters with a mass of ≳ 10 14 M⊙ . We also investigate the correlation between LAE overdensity and Lya rest-frame equivalent width (EW), because the cosmological Lyα RT model suggests that a slope of EW-overdensity relation is steepened towards the epoch of cosmic reionization (EoR), due to the existence of the ionized bubbles around galaxy overdensities easing the escape of Lyα emission from the partly neutral intergalactic medium. The available HSC data suggest that the slope of the EW-overdensity correlation does not evolve from the post-reionization epoch z = 5.7 to the EoR z = 6.6 beyond the moderately large statistical errors.